Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bandung Barat - Munawaroh, Siti; Wulandari, Widuri (Department of Political Science - Universitas Sains Al-Qur’an, 2024)
This study aims to determine and analyze how much influence service quality has on public satisfaction at the Population and Civil Registration Office of West Bandung Regency. The research method in this study is quantitative descriptive, with the Independent Variable being Service Quality with indicators of Tangible, Reliability, Responsiveness, Assurance, Empathy. While the Dependent Variable is Public Satisfaction, with indicators. Conformity to expectations, Interest in revisiting, Willingness to recommend. Data collection techniques by means of surveys, observation and documentation. Based on the results of the study and discussion regarding the influence of service quality on public satisfaction at the Population and Civil Registration Office, it has an influence. Service Quality can explain the dependent variable, namely Public Satisfaction by 38.7%, while the remaining 61.3% is explained by other factors or variables. Thus, H0 is rejected and Ha is accepted.